Business management strategies in the food industry from a tourism perspective - Wibowo, Sukarno; Purnama, Rusna; Hidayat, Nova Maulidan; Riyani, Dewi; Avinda, Baby Bianca (Keynesia : International Journal of Economy and Business, 2025)
This study aims to analyze, explore the Business Management Strategy of Culinary Business in Tourism in Cimuja Cimalaka, Sumedang Regency, West Java. This village has great potential for the development of culinary ecotourism. The research conducted is field research using qualitative research. Qualitative research uses observation and interviews in collecting data in the field, the data sources used are primary data and secondary data. The information in this study amounted to 33 people, namely 1 restaurant owner and 32 employees of Saung Teko Restaurant which includes 4 components, namely planning, organizing, actuating and controlling. Planning is done with Service to Customers who come to the Restaurant and serving food according to orders so as not to be excessive so that quality is maintained. Second, Organizing here is in the form of Employees providing services that have been received will be given guidance before working, such as being guided on how to serve well and serving consumer food will maintain its quality. Third, Actuating here is guiding each employee in carrying out each of their duties, starting from working on time. Fourth, Controlling is in the form of directly supervising employees and reprimanding them directly if there is a mistake made by employees. Business management strategies in accordance with tourism principles and effective marketing strategies are the key to successful tourism development.